2012
DOI: 10.1016/j.ajhg.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Linkage and Association Analyses Implicate FASN in Predisposition to Uterine Leiomyomata

Abstract: Uterine leiomyomata (UL), the most prevalent pelvic tumors in women of reproductive age, pose a major public health problem given their high frequency, associated morbidities, and most common indication for hysterectomies. A genetic component to UL predisposition is supported by analyses of ethnic predisposition, twin studies, and familial aggregation. A genome-wide SNP linkage panel was genotyped and analyzed in 261 white UL-affected sister-pair families from the Finding Genes for Fibroids study. Two signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 35 publications
(36 reference statements)
4
96
2
Order By: Relevance
“…However, little is known on the associations between these SNPs and cancer risk as well as patient prognosis. It has been reported that SNP rs4247357 in the FASN gene is associated with the risk of uterine leiomyomata (Eggert et al, 2012). In addition, Nguyen PL et al have reported that SNP rs1127678 in the FASN gene is associated with the risk and mortality of prostate cancer (Nguyen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known on the associations between these SNPs and cancer risk as well as patient prognosis. It has been reported that SNP rs4247357 in the FASN gene is associated with the risk of uterine leiomyomata (Eggert et al, 2012). In addition, Nguyen PL et al have reported that SNP rs1127678 in the FASN gene is associated with the risk and mortality of prostate cancer (Nguyen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also discussed the relationship between polymorphisms of DNL genes and development and prognosis of cancers (Nguyen et al, 2010;Eggert et al, 2012). However, no studies have focused on the association between polymorphisms of ACLY, ACC and FASN and NSCLC prognosis until now.…”
Section: Introductionmentioning
confidence: 99%
“…No candidate susceptibility genes have consistently emerged from the few linkage scans and genome-wide association studies (GWAS) reported so far (811). Exome sequencing in 18 UL tumors and matched normal myometria has implicated the mediator complex subunit 12 ( MED12 ) gene (12) and further examinations of exomes and gene-expression profiling in a set of 38 UL and matched myometria led to the hypothesis that a chromothripsis-like event drives the pathogenesis of UL leading to translocations of the HMGA2 and RAD51B loci and to other chromosomal aberrations including the COL4A5-COL4A6 locus (13).…”
Section: Introductionmentioning
confidence: 99%
“…We conducted an independent follow-up fine mapping of extended candidate regions that were identified in a genome-wide linkage scan in ASP (11) and mapping by admixture linkage disequilibrium (MALD) in the Black Women’s Health Study (BWHS)(10). We report data in both the African American (AA) and European American (EA) study groups implicating variant members of the collagen gene family encoding components of the extracellular matrix suspected in fibrosis (19).…”
Section: Introductionmentioning
confidence: 99%
“…Excepting for amino acid change, SNPs directly affect gene functions through various translational or post-translational mechanisms, such as altering miRNA binding, gene splicing, protein folding or mRNA degradation (Chamary et al, 2006). There were several studies have investigated the association between polymorphisms of DNL genes and development or prognosis of cancers (Nguyen et al, 2010;Eggert et al, 2012). Previously, our group has identified that SNPs in ACLY and FASN genes are significantly associated with clinical outcomes in non-small cell lung cancer patients (Jin et al, 2014).…”
mentioning
confidence: 99%